Effect of micro‐perforated film packing on physicochemical quality and volatile profile of button mushroom (Agaricus bisporus) during postharvest shelf‐life. Issue 7 (25th April 2022) - Cheng, Yujiao; Wei, Yaqing; Zhang, Min; Wang, Hua
Abstract: The perishable characteristics of button mushrooms ( Agaricus bisporus ) decrease the physicochemical and change the flavor profile, affecting consumer purchase. In this study, button mushrooms were separately stored in the package with 0, 2, 4, 8, and 16 perforations for 8 days at 10°C, and whether the micro‐perforated film packing delayed button mushrooms the changes in physicochemical quality and volatile profile was investigated. The results showed that 0 perforation packages could maintain the weight and firmness of button mushrooms. Micro‐perforated film packing was found effective to decrease the browning index of button mushrooms during shelf‐life. In addition, mushrooms in micro‐perforation film packing had a lower concentration of 3 off‐flavor compounds (2‐methylbutanal, 3‐methylbutanal, and ethanol) and a higher concentration of 13 mushroom characteristic flavor compounds than that in 0 perforation film when stored for 8 days. The 8 perforations groups had the most varieties of aroma impact compounds (odor active values, OAV ≥ 1), which contributed to the flavor profile of button mushrooms. It is concluded that film with 8 perforations could create an atmosphere condition to maintain the physiology quality and volatile profile of button mushrooms during shelf‐life. Novelty impact statement: The firmness of the mushroom was maintained due to the ethanol and low oxygen. 2‐Methylbutanal, 3‐methylbutanal, and ethanol were the main off‐flavor compounds.